2015 International Conference on Computational Intelligence and Networks 2015
DOI: 10.1109/cine.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Adaptive Beamforming Techniques in Smart Antenna Using LMS Algorithm and Its Variants

Abstract: This paper presents a comparative study of beamforming techniques using least mean square (LMS) algorithm and its variants, like, normalized least mean square (NLMS) algorithm and sign least mean square (SLMS) algorithm. The accuracy of beam generation toward the direction of arrival (DoA) and null generation toward the interferer, depends on the value of step size parameter used in the algorithm. Beamwidth and side lobe levels (SLL) are also compared for these three algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 13 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…It is a mechanism of using the sensor nodes in the right fashion to deliver the data to the right resource and send the jamming signal towards the wrong resource. The generation of maximum radiation towards the actual user and side lobe towards the interference user is called Beam forming [32]- [38]. There are many techniques which are used to achieve beam forming like autocorrelation and cross-correlation computation using Sample Matrix Inverse, reducing the mean square error by making use of Least Mean Square The antenna arrays which are distributed in nature will send selective beams towards the receiver which will increase the transmission range the amount of transmission power can be decreased by nodes due to energy dissipation being shared among the transmitting devices.…”
Section: Beam Formingmentioning
confidence: 99%
“…It is a mechanism of using the sensor nodes in the right fashion to deliver the data to the right resource and send the jamming signal towards the wrong resource. The generation of maximum radiation towards the actual user and side lobe towards the interference user is called Beam forming [32]- [38]. There are many techniques which are used to achieve beam forming like autocorrelation and cross-correlation computation using Sample Matrix Inverse, reducing the mean square error by making use of Least Mean Square The antenna arrays which are distributed in nature will send selective beams towards the receiver which will increase the transmission range the amount of transmission power can be decreased by nodes due to energy dissipation being shared among the transmitting devices.…”
Section: Beam Formingmentioning
confidence: 99%
“…In figure 7 and figure 11, VSLMS algorithm does not work properly for step-size value of 0.04 as it is found that LMS algorithm does not work for higher values of step-size parameter [13] and so the variable step-size LMS algorithm. The performances of VSLMS and VSNLMS algorithms for main beam direction, null depth at desired null direction and maximum side lobe level (SLLmax) are compared in Table 2.…”
Section: Asian Journal Of Applied Sciences (Issn: 2321 -0893) Volume mentioning
confidence: 99%
“…In the SISO case, either the transmitter or the receiver uses a single antenna for the communication process; while in the MIMO, an antenna array is employed. In literature, it has been demonstrated how the use of directional antennas and the most recent smart antenna systems (SAS) technology is capable of significantly allowing high quality of service (QoS) requirements in spite of the omnidirectional systems that foresee limited functionalities [6,7]. However, these solutions are unlikely to satisfy the requirements for 5G wireless communication systems technology.…”
Section: Introductionmentioning
confidence: 99%